Dukungan Sosial untuk Mendukung Keberhasilan Pemberian ASI Eksklusif pada Ibu Bekerja Sebagai Upaya Pencegahan Stunting di Indonesia - Rufaida Adya Nur Avianti Ulya (Media Gizi Kesmas, 2023)
Background: The current stunting prevalence rate in Indonesia is below the target of the National Medium Term Development Plan (RPJMN) 2020-2024, in which accounted 21.1% in 2021 and 14% in 2024. One of the efforts to eradicate stunting is exclusive breastfeeding. On the other hand, working mothers are more prone to fail to provide exclusive breastfeeding, as a result, the risk of stunting in infants with working mothers is higher. Thus, to promote exclusive breastfeeding for working mothers is social support   Objectives: To review various literatures in the form of journal articles that discuss social support and the success of exclusive breastfeeding for working mothers in Indonesia. Methods: This research method was qualitative analysis by doing a literature review derived from published research articles. Articles acquired through Google Scholar database, Neliti, Pubmed and Science Direct. Article searches are using variations and combinations of the following Indonesian words "Dukungan”, "ASI Ekslusif”, and "Ibu Bekerja”, while article searches in English use the keywords "Support”, "Breastfeeding”, "Mother”, "Woman”, "Workers”, and "Employments”. Discusssion: Ten articles were obtained from the selection of inclusion and exclusion criteria. The result shows that five sources of social support that are related to the success of exclusive breastfeeding for working mothers are the support from these following parties, husband, family (other than husband), caregiver, supervisor or co-worker and health worker support. Conclusions: Social support for breastfeeding mothers who work can help the success of exclusive breastfeeding for toddlers.